DENTAL STATUS IN PATIENTS WITH DEFICIENCY OF SECRETORY IMMUNOGLOBULIN A IN ORAL FLUID - G.M. Sylenko; T.V. Mamontova; V.A. Dubin; P.M. Skrypnykov; Y.I. Sylenko (Ukrainian Medical Stomatological Academy, 2015)
Generalized periodontitis is a leader in the structure of dental diseases and dental remains an unresolved problem. According to different authors and WHO GP prevalence among people 45-60 years old is 96-100%. SIgA deficiency occurs in 17% of the population, its lack of saliva can lead to disruption of the relationship between oral microflora, especially its opportunistic forms and microorganism. In the result, it increases the numbers of organisms and their corrosive properties and appearances of forms. This condition occurs rare in healthy people or does not occur at all. The purpose of the article is to assess dental status of patients with deficiency of secretory immunoglobulin A in oral fluid. The study involved 40 patients with generalized periodontitis deficient sIgA, which, depending on the age group, divided into 3 groups. The first group included 12 patients aged 20-35 years, the second - 13, age 36-50, the third - 15 patients, aged 51-65 years. The control group consisted of 10 patients with normal content of sIgA aged 22 to 50 years. The state of immunity oral mucosa was conducted to determine the level sIgA in oral fluid by solid phase ELISA. Oral liquid were collected in the morning on an empty stomach and in the volume of 0.5 ml, and then frozen at a temperature of -8 degrees Celsius. The level of sIgA oral fluid was studied by the using of reagents set of "secretory IgA-ELISA", Russia. All patients was made the standard dental examination that included determining the prevalence and intensity of dental caries index CPV, evaluation of hygienic condition of oral hygiene index using GV (JC Green, JR Vermillion, 1964). Periodontal lesions spent determining periodontal indices - AI (A.Russell, 1956, Leus), the index of bleeding gums (Muhlemann HP, 1971), papillary-marginally-alveolar index (PMA, Parma C., 1960). It was mentioned the structure of lesions of the oral mucosa. All the results recorded in the history of the dental patient (form 043 / y) and specially designed map individual patient. Statistical analysis of the results was performed the using of the method of variation statistics for each row of values to the calculation arithmetic mean value (M), errors arithmetic mean value (m), Student factor (T) and the probability of differences at p <0.05. The article highlights the main indicators of dental status of patients with deficiency of secretory immunoglobulin A in oral fluid. It is shown that deficiency of humoral immunity factors accompanied by increased oral hygiene index indicator, the index CPU and periodontal index is directly proportional to the age of patients compared with patients with normal oral fluid sIgA content. Our studies have shown that in patients with age-deficient sIgA observed a significant decrease in its level especially in patients 3 groups. Analysis of the studies proves the important role of humoral immunity mouth, particularly secretory immunoglobulin A in the causing of inflammation in the periodontal tissues. Obtained facts require the need to develop and improve existing methods of treatment and prevention particularly generalized periodontitis in patients with congenital deficiency of sIgA.